Fazlur Rahman düşüncesinde metod meselesi - Söylemez , Mehmet Raif (My University, 2019)
ÖZETBu tez, bir düşünür olarak Fazlur Rahman’ın modern dünyada yaşayan Müslümanların Kur’an-ı Kerim’i doğru/ nesnel anlama sorunları için geliştirme iddiasında olduğu metod meselesinin onun düşüncesindeki yerini incelemektedir.Fazlur Rahman, geleneksel yorumlama metodlarının Kur’an-ı Kerim’i doğru/ nesnel anlamayı sağlamada yetersiz olduklarını ifade ettikten sonra, tamamen yeni olmamakla birlikte bir metod geliştirmeye çalıştığını ifade etmektedir. O, açıkça ifade etmemekle birlikte metodunu tarihselci düşünsel bir zeminde inşa etmektedir. Ancak tarihselciliğin kutsal bir metne uygulanmasının doğurabileceği sorunları açıklamamaktadır. Tez, Fazlur Rahman’ın metod meselesinin, onun dini kavramları anlamasına nasıl etki ettiğini, bu bağlamda klasik metafizik ile olan bağını da araştırmaktadır.Fazlur Rahman, Metod, Tarihselcilik, Nesnel Anlama, Metafizik.

ABSTRACTMasters With ThesisTHE METHOD ISSUE IN FAZLUR RAHMAN THOUGHTMehmet Raif SÖYLEMEZT.C. University of MarmaraInstitute of Social SciencesDepartment of Philosophy and ReligionThis thesis examines the position of the method issue in Fazlur Rahman’s, as a thinker, thoughts which claims to develop fort he problems of Qur’an’s correct/ objective understanding by Muslims living in modern World.Fazlur Rahman, after expressing that the traditional interpretation methods are insufficient in ensuring the correct/ objective understanding of the Qur’an, he says that he has tried to develop a method that is not completely new. He does not make it clear, but constructs his method on a historicist intellectual base. However, he does not explain the problems that can be casued by the application of historicism to a sacred text.The thesis also studies how Fazlur Rahman’s methodology influences his understanding of religious concepts, and his connections with classical metaphysics in this context.Fazlur Rahman, Method, Historicism, Objective Understanding, Metaphysic.
Keywords: 20. yy; 20th century; Criticism and interpretation; Eleştiri ve yönetim; Fazlur Rahman Fazlur Rahman; Hermeneutics; Islam; İslam; Kur’an-ı Kerim; Qurʼan; Rahman, Fazlur, 1919-1988; Tefsirler